Dealloying of gold–copper alloy nanowires: From hillocks to ring-shaped nanopores - Chauvin, Adrien; Delacôte, Cyril; Boujtita, Mohammed; Angleraud, Benoit; Ding, Junjun; Choi, Chang-Hwan; Tessier, Pierre-Yves; El Mel, Abdel-Aziz (Beilstein Journal of Nanotechnology, 2016)
We report on a novel fabrication approach of metal nanowires with complex surface. Taking advantage of nodular growth triggered by the presence of surface defects created intentionally on the substrate as well as the high tilt angle between the magnetron source axis and the normal to the substrate, metal nanowires containing hillocks emerging out of the surface can be created. The approach is demonstrated for several metals and alloys including gold, copper, silver, gold–copper and gold–silver. We demonstrate that applying an electrochemical dealloying process to the gold–copper alloy nanowire arrays allows for transforming the hillocks into ring-like shaped nanopores. The resulting porous gold nanowires exhibit a very high roughness and high specific surface making of them a promising candidate for the development of SERS-based sensors.
Keywords: copper; dealloying; gold; hillocks; nanoporous